Insecticide-treated nets ownership and utilization among under-five children following the 2010 mass distribution in Burkina Faso - Diabaté, Souleymane (BioMed Central, 2014)
BACKGROUND: Periodic mass distributions contribute significantly to universal access to insecticide-treated nets (ITNs). However, due to the limited number of nets distributed, needs remain unsatisfied, particularly in large households. METHODS: This study was conducted in Kaya health district following the 2010 mass distribution of ITNs in Burkina Faso. Data were collected on the socio-economic and geo-spatial characteristics and ITN possession and utilization levels of 2,004 households. The study explored: 1) ITN access, in terms of intra-household saturation with ITNs (households with at least one ITN for every two members) correctly installed and in very good physical condition; and 2) factors influencing the decision to place under-five children under a net. Particular attention was given to vector control activities undertaken by mothers. RESULTS: Of the 2,004 households, 90% possessed at least one ITN. However, intra-household saturation with ITNs was below 60% in small households and below 20% in large ones (>6 members). Crude proportion ratios comparing possession and levels of intra-household saturation with ITNs varied between 1.5 (small households) and 7.8 (large households). The proportions of households with ITNs for every two members that were correctly hung or in very good physical condition ranged from 0% to 6.5% in large households and 27.8% to 40.7% in small ones. ITN use to protect under-five children was lower in large households; it was significantly higher when there was at least one ITN for every two members. In large households, it was significantly higher when a child had experienced an episode of any illness in the previous two weeks and when the mother had taken actions to control vector proliferation. In small households, ITN use was significantly higher in families with agricultural land and children aged 12–23 months. CONCLUSION: Ownership rates were high, but real access to bed nets remained limited. The allocation process disadvantages large families. Real access to bed nets implies they are available, properly installed, and in good condition. More post-campaign awareness-raising activities targeting preventive practices in households could foster more effective ITN use.